The Effect of Community Perception of the Existence of Tourism Object Celosia Park on Job and Business Opportunities with Self-Efficacy as the Moderating Variable (Journal of Economic Education, 2022)
Park tourism object on job and business opportunities with self- efficacy as the moderating variable. With a tourism object in an area, it is hoped that it can improve the community's economic level around the tourism object by providing opportunities to work and open a business. However, in reality, the changes that occur are not always as expected. Most of them only provide profit from the investor's side. The approach used in this study was a quantitative approach. This study's sample was 98 residents who lived in 3 villages, i.e., Talun, Ngipik, and Tarukan. The sampling technique used was random cluster sampling, using the calculation of the Slovin formula. The data collection techniques/instruments were questionnaires, interviews, and direct observation. The data analysis technique used was moderate regression. The results showed that the public perception of the Celosia Flower Park tourism object's existence had a positive and significant effect on job opportunities by 40.5% and on business opportunities by 51.9%. The self-efficacy variable positively and significantly moderated the influence of public perceptions of the existence of the Celosia Flower Park tourism object on job opportunities. The self-efficacy variable moderates positively and significantly the influence of public perceptions of the existence of the Celosia Flower Park tourism object on business opportunities.